Sensory and Chemical Quality of Kombucha Fermented Whey with the Addition of Subang Pineapple Juice - Suciati, Fitri; Triastuti, Desy; Permadi, Edy (JURNAL ILMIAH PETERNAKAN TERPADU, 2025)
Kombucha fermented whey is whey fermented products which utilize kombucha inoculum as starter. The addition of subang pineapple juice is expected to improve the taste of kombucha fermented whey. This research aimed to determine the sensory and chemical quality of kombucha fermented whey with the addition of subang pineapple juice. This research used 1-factor Completely Randomized Design, namely the variation ratio of kombucha fermented whey and subang pineapple juice (kombucha fermented whey:subang pineapple juice) with 5 treatments which were as follows: P1 (100:0), P2 (95:5), P3 (90:10), P4 (85:15), and P5 (80:20). The testing of sensory and chemical quality, included hedonic test, pH, Total Soluble Solid (TSS), Titratable Acidity (TA), and vitamin C content. The sensory quality data was analyzed using Kruskal-Wallis test and the chemical quality data was analyzed using Analysis of Variance then further analyzed by Duncan Multiple Range Test. Research results showed the variation ratio of kombucha fermented whey and subang pineapple juice siginficantly affected (P<0.05) flavor, aroma, viscosity and overall aceptability, however it did not affected the color, whereas in chemical quality, the variation ratio of kombucha fermented whey and subang pineapple juice significantly affected (P<0.05) the TSS and vitamin C content, however did not affect (P>0.05) the pH and TA. The best treatment was P5 with the ratio of 80:20 (kombucha fermented whey : subang pineapple juice).